2013
DOI: 10.1103/physrevlett.110.120401
|View full text |Cite
|
Sign up to set email alerts
|

Maximally Epistemic Interpretations of the Quantum State and Contextuality

Abstract: We examine the relationship between quantum contextuality (in both the standard Kochen-Specker sense and in the generalized sense proposed by Spekkens) and models of quantum theory in which the quantum state is maximally epistemic. We find that preparation noncontextual models must be maximally epistemic, and these in turn must be Kochen-Specker noncontextual. This implies that the Kochen-Specker theorem is sufficient to establish both the impossibility of maximally epistemic models and the impossibility of pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
128
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 23 publications
3
128
0
Order By: Relevance
“…Furthermore, we show that restricted preparation contextuality of quantum theory leads to its limited nonlocal behavior as depicted in the Cirel'son bound. Therefore, our result brings the qualitative connection between preparation contextuality and nonlocality explored in [12][13][14] to a quantitative footing.…”
Section: Arxiv:150605174v2 [Quant-ph] 12 Sep 2015mentioning
confidence: 57%
See 3 more Smart Citations
“…Furthermore, we show that restricted preparation contextuality of quantum theory leads to its limited nonlocal behavior as depicted in the Cirel'son bound. Therefore, our result brings the qualitative connection between preparation contextuality and nonlocality explored in [12][13][14] to a quantitative footing.…”
Section: Arxiv:150605174v2 [Quant-ph] 12 Sep 2015mentioning
confidence: 57%
“…It was then shown that mixed preparations (density matrices) in quantum theory exhibit preparation contextuality [9,12]. Interestingly, invoking another non-classical concept called steering [10,11] along with this new idea of preparation contextuality one can establish nonlocality of QM without using any Bell type inequalities; it has been shown that nonlocality of some hidden variable models, underlying QM, directly follows from the steerability of bipartite pure entangled states and the preparation contextuality of mixed states [12][13][14].The traditional definition of contexuality address to only the contexts of projective measurements, which has been studied in much depth [15,16]. However, generalized notion of contextuality developed by Spekkens define three different types of contexts: measurement (generalized), preparation, and transformation contexts [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In Refs. [12,13], the question is raised whether ψ-epistemic models can reproduce quantum predictions given an assumption about the extent to which the epistemic states overlap.Refs. [12,13] are the most direct precursors to this work, since here we are also concerned with the extent to which the distributions µ ψ and µ φ can overlap in models which recover the predictions of quantum theory.…”
mentioning
confidence: 99%